The study of conformity of the pharmaceutical service in Puskesmas Bogor City towards PMK No. 74, 2016 - Nhadira Nhestricia; Hero Prasetio Kusworo; Lusi Agus Setiani (Universitas Islam Indonesia, 2023)
Background: Improving the quality of pharmaceutical services requires a change in the old product-oriented paradigm (drug-oriented) into a new patient-oriented paradigm (patient-oriented) by executing pharmaceutical care. Improving the quality of pharmaceutical services to people who have direct contact through primary health care as the first-level health facility refers to PMK No. 74 of 2016.Objective: This study aims to determine the description of the implementation of pharmaceutical service standards at the Primary Health care facility in Bogor City for the 2022 period based on PMK No. 74 of 2016.Method: This study used a descriptive approach with an exploratory research type. Retrieval of data using questionnaire instruments and observation checklists The research was conducted for six months, from April to September 2022. The population in this study (24 primary health care and 24 pharmacy installation heads as respondents).Results: Based on the research results, the description of the implementation of pharmaceutical service standards at Bogor City Primary Health Care, based on PMK No. 74 of 2016, for the 2022 period showed that the average value of the questionnaire and observation instruments in the fields of management of pharmaceutical supplies and medical consumables (BMHP), clinical pharmacy services, and pharmaceutical quality control had successive values of 94.87, 85.5, and 100% (very good). The results of the value of the availability of pharmaceutical human resources were 95.83% (very good).Conclusion: The conclusion of the implementation of pharmaceutical services at the Bogor City Primary Health Care is in accordance with the pharmaceutical service standards at the Primary Health Care based on PMK No. 74 of 2016. Intisari Latar belakang: Peningkatan kualitas pelayanan kefarmasian menuntut adanya perubahan paradigma lama yang berorientasi terhadap produk (drug oriented) menjadi paradigma berkembang pada era saat ini yang berorientasi pada pasien (patient oriented) dengan melaksanakan pharmaceutical care. Peningkatan kualitas pelayanan kefarmasian pada masyarakat yang berhubungan langsung melalui puskesmas sebagai fasilitas kesehatan tingkat pertama yang merujuk pada PMK No. 74 Tahun 2016. Tujuan: Penelitian ini bertujuan untuk mengkaji kesesuaian implementasi standar pelayanan kefarmasian di Puskesmas Kota Bogor terhadap PMK No 74 Tahun 2016.Metode: Penelitian ini menggunakan pendekatan deskriptif dengan jenis penelitian eksploratif. Pengambilan data menggunakan instrumen kuisioner dan daftar tilik observasi. Penelitan dilakukan selama 6 bulan sejak April – September 2022. Populasi dalam penelitian ini adalah kepada kepala instalasi farmasi di seluruh Puskesmas Kota Bogor.Hasil: Implementasi standar pelayanan kefarmasian Puskesmas Kota Bogor berdasarkan PMK No. 74 tahun 2016 periode 2022 didapatkan hasil nilai rata-rata instrumen kuesioner dan observasi di bidang Pengelolaan Sediaan Farmasi dan Bahan Medis Habis Pakai (BMHP), pelayanan farmasi klinik serta pengendalian mutu kefarmasian memiliki nilai berturutu-turut sebesar 94,87; 85,5; dan 100% (sangat baik). Hasil nilai ketersediaan SDM kefarmasian sebesar 95,83% (sangat baik). Kesimpulan: Pelayanan kefarmasian di Puskesmas Kota Bogor telah sesuai dengan PMK No. 74 Tahun 2016.Kata kunci: pelayanan farmasi; permenkes; puskesmas